The evaluation of authentic assessment implementation of Curriculum 2013 in Elementary School - Wangid, Muhammad Nur; Mustadi, Ali; Senen, Anwar; Herianingtyas, Nur Luthfi Rizqa (Graduate School, Universitas Negeri Yogyakarta, 2017)
This research was aimed to evaluate the implementation of authentic assessment of elementary school in Province of Yogyakarta and also to know the obstacles of its implementation. This was an evaluative research by a Stake's evaluation model approach. The results of observation in compare to the standard of assessment should be criteria to determine the succeed. This research subjects were elementary teachers in Province of Yogyakarta. Observation, interview, and documentation were used to gather data. The research showed that: (1) Planning (antecedents) stage or understanding towards authentic assessment planning has not been fulfilled the standard to be categorized as Good with percentage of 68.75%; (2) Process (transaction) or implementation stage that obtained 63.41% in percentage was classified in Good category; (3) Outcome stage or authentic assessment report showed 68.48% in percentage and should be categorized Good. The implementation of authentic assessment in Province of Yogyakarta elementary schools have not 100% met the standard. Therefore, results from this research finding were expected to be tools to improve performance from all stakeholders.